Angela Merkel : The Chancellor and Her World - Kornelius, Stefan; Translated by Bell, Anthea and Moncrieff, Christopher (London Alama Books, 2013)
This authorized biography sheds light on the person behind the politician. As well as explaining how Angela Merkel's world view was shaped and influenced by her background and ideology, Stefan Kornelius's lively account discusses her personal relations with David Cameron, Barack Obama or Vladimir Putin.
Keywords: Germany -- Diplomatic Relations -- Women politicians -- Politics and government -- Women prime ministers -- Germany -- Biography